Respuesta agro-fisiológica a la fertilización nitrogenada, y respuesta de uso del nitrógeno en quínoa en una región interandina de Loja - Oviedo Castillo, Wagner Adrian (2023)
Quinoa is a crop of Andean origin that has been gaining importance in recent years due to its great capacity to adapt to different environments and, on the other hand, its high nutritional content. In Ecuador it is grown mainly in the inter-Andean region. National yields are considered low; at the level of small producers, data have been reported that do not exceed one ton per hectare. Poor agronomic management is one of the causes of these yields. In this context, nutrition, and in particular the use of nitrogen (N), is essential to increase production. The present study evaluated the productive response to nitrogen fertilization of the quinoa variety Tunkahuan, in order to determine an optimum dose as a function of N dose and the efficiency of use of this nutrient, for which five doses (treatments) of N (0, 50, 100, 200 and 400 kg N ha-1) were applied. The experiment was established in a completely randomized design, and the data were analyzed with analysis of variance and Tukey 5 % multiple comparison tests. Yields ranged from 1.46 to 3.41 t ha-1, with the 200 kg N ha-1 dose having the highest yield. Grain protein content ranged from 14.80 % to 17.01 %. The highest agronomic efficiency was found with 50 kg N ha-1 with 13.66 kg of grain per kg N applied. For physiological efficiency, the application of 200 kg N ha-1 produced the highest value with 20.20 kg of grain per kg of N absorbed. Recovery efficiency and N use efficiency showed similar dynamics, with the application of 50 kg N ha-1 producing the highest efficiency with 82.46 % and 39.72 kg of grain per kg of N applied. Under the conditions of this experiment, the optimum agronomic dose was 135.00 kg N ha-1 to achieve a yield of 3 t ha-1. Key words: yield, agronomic efficiency, physiological efficiency, optimum dose.